Self-assembly and spectroscopic fingerprints of photoactive pyrenyl tectons on hBN/Cu(111) - Zimmermann, Domenik M (Beilstein J Nanotechnol, 2020)
The controlled modification of electronic and photophysical properties of polycyclic aromatic hydrocarbons by chemical functionalization, adsorption on solid supports, and supramolecular organization is the key to optimize the application of these compounds in (opto)electronic devices. Here, we present a multimethod study comprehensively characterizing a family of pyridin-4-ylethynyl-functionalized pyrene derivatives in different environments. UV–vis measurements in toluene solutions revealed absorption at wavelengths consistent with density functional theory (DFT) calculations, while emission experiments showed a high fluorescence quantum yield. Scanning tunneling microscopy (STM) and spectroscopy (STS) measurements of the pyrene derivatives adsorbed on a Cu(111)-supported hexagonal boron nitride (hBN) decoupling layer provided access to spatially and energetically resolved molecular electronic states. We demonstrate that the pyrene electronic gap is reduced with an increasing number of substituents. Furthermore, we discuss the influence of template-induced gating and supramolecular organization on the energies of distinct molecular orbitals. The selection of the number and positioning of the pyridyl termini in tetrasubstituted, trans- and cis-like-disubstituted derivatives governed the self-assembly of the pyrenyl core on the nanostructured hBN support, affording dense-packed arrays and intricate porous networks featuring a kagome lattice.